Changes in Cd, Cu, Ni, Pb and Zn Fractionation and Liberation Due to Mussel Shell Amendment on a Mine Soil - Fernández-Calviño, David; Pérez-Armada, Lorena; Cutillas-Barreiro, Laura; Paradelo-Núñez, Remigio; Núñez-Delgado, Avelino; Fernández-Sanjurjo, María J.; Álvarez-Rodriguez, Esperanza; Arias-Estévez, Manuel (Land degradation & development, 2016)
Mining activities are related to relevant environmental pollution issues that should be controlled. We used sequential extractions to fractionate Cd, Cu, Ni, Pb and Zn retained on unamended or mussel shell‐amended mine soil samples, all of them treated with a mixture of the five heavy metals (total metal concentration of 1·57 mmol L−1), after 1, 7 and 30 days of incubation. In addition, we used the stirred flow chamber technique to study the release of each of the five heavy metals from these different unamended and shell‐amended soil samples. The results indicate that the shell amendment caused a decrease in the most soluble fraction, while increasing the most recalcitrant (least mobile) fraction. With equivalent implications, the stirred flow chamber experiments showed that mussel shell amendment was associated to a decrease in heavy metal release and increased retention. The highest mussel shell dose and incubation time caused the most relevant changes in pH values and thus in metal retention, also indicating the importance of pH modifications in the mechanism of retention acting in the amended samples. In view of these results, the use of mussel shell amendment can be encouraged to increase heavy metal retention in acid mine soils, in order to minimise risks of environmental pollution. Copyright © 2016 John Wiley & Sons, Ltd.